Optimalising Digital Marketing and Service Quality to Enhance Customer Loyalty in the Digital-Economy Era - Ferianto, Maidar; Widodo, Slamet; Siregar, Nurafrina (PT Inovasi Pratama Internasional, 2025)
This study investigates how digital-marketing practices and service-quality improvements jointly foster customer loyalty within Indonesia’s rapidly expanding digital economy. A systematic quantitative literature review combined with meta-analytic synthesis was employed to integrate findings from peer-reviewed empirical studies published between 2018 and 2025 that applied structural-equation modelling (SEM) or partial least squares (PLS). The review confirms that (1) digital-marketing factors—especially social media engagement, personalised content and marketing innovation—and (2) electronic service-quality (e-SERVQUAL) dimensions such as assurance, responsiveness and website usability exert significant positive effects on customer loyalty (path coefficients range β = 0.24–0.89, p < 0.05). Customer satisfaction, perceived value and trust consistently mediate these relationships. The findings offer managers evidence-based guidelines to balance promotional investments with service-quality enhancements, thereby sustaining loyalty and competitive advantage